Detecção e genotipagem do papilomavirus humano em amostra do colo do útero de adolescentes do Distrito Sanitário Noroeste do município de Goiânia, Goiás - Daud, Lyana Elias Santos (2005)
Background: Human Papillomavirus (HPV) infection is a strong predictor for cervical cancer development. Some HPV types are considered at high-risk and associated with pre-malignant lesions and cervical cancer. Genital HPV infection is highly prevalent in sexually active young women. Actually PGMY09/11 primer system associated with Restriction Fragment Length Polymorphism (RFLP), hibridization or DNA sequencing is one of the most sensitive methods for detecting and typing HPV-DNA in genital samples. Objectives: To detect and identify HPV-DNA genotypes in genital specimens among sexually active female adolescents from Distrito Sanitário Noroeste, Goiânia. Methods: We performed a cross-sectional study among 432 sexually active female adolescents (15-19 years), randomly selected at Distrito Sanitário Noroeste, Goiânia, and served by the Family Health Program. HPV-DNA was detected by PCR assay, in endocervical samples, using the PGMY09/11 consensus primer set. The presence of amplifiable DNA was assessed with -globin primers (PCO3/PCO4). Amplicons generated with PGMY primers were typed with the line blot assay (PGMY-line blot) and RFLP. Results: HPV-DNA was detected in 121 samples yielding a 28% prevalence (95% CI 23.8- 32.5). All samples yielded a -globin amplimer, confirming the DNA adequacy. Thirty different HPV genotypes were identified, the high risk genotypes frequently found being: HPV-16 (6,7%); followed by HPV-51 (5,1%); HPV-31 (4,6%); HPV-52 (4,2%) and HPV-18 (3,5%). PGMY-line blot test identified 54 cases of infection caused by multiple genotypes. The genotypes 16, 51, 18, 53 and 52 were the most frequently associated with cervical co- infection with multiple HPV types. Conclusions: A high prevalence of HPV-DNA was found and a broad spectrum of HPV genotypes was identified, predominantly high risk HPV genotypes. A high frequency of multiple HPV infections was found in the studied population.